P-232 'pic' your patient: development of a multi-professional handover tool. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Mills, Mark; Robinson, Claire; Chapman, Laura
Abstract : Background: In a 26-bedded hospice it was recognised that handovers were excessive and inefficient. A review of practice revealed that they were occurring over 15 times per day with different professions present at each one. The Multi-disciplinary team (MDT) felt frustrated, recognising that the handovers reduced time for direct patient contact but still did not ensure timely sharing of crucial information. Staff wanted a single, efficient MDT handover to identify key patient issues. Method: Current available tools were reviewed including SBAR (Haig, Sutton & Whittington, 2006) (Situation, Background, Assessment, and Recommendation) but were found to be unsuitable for the hospice environment. The PIC acronym was created to facilitate nursing presentation of each patient. This prompted a discussion of: Plan (Is the patient going anywhere today? Are we working towards getting them to their preferred place of care?); Involvement (Are they being seen by the appropriate MDT members?); Concerns (Are you concerned about the patient or their family?). The PIC tool was used at the newly launched 'Huddle' – a handover led by a senior nurse and designated consultant, with a representative from each discipline of the MDT occurring each weekday morning from 0900–0910. Results: Informal feedback from staff suggested that the Huddle and PIC tool enabled more organised and efficient discharges. It was useful to give a view of the complexity of the patients throughout the hospice and guide admissions. A formal survey of the MDT is being carried out, with results available by October 2017. Conclusion: Huddle is reducing the number of handovers each day and increasing the productivity of the hospice. This has benefits for swift discharge and assessing the needs of patients with complex problems. An unintended benefit has been improved nursing confidence in their presenting skills.